+0  
 
0
533
1
avatar

Given f(x)=x^2-1 and g(x)=x-3 g(f(2))

 Oct 30, 2014

Best Answer 

 #1
avatar+2353 
+5

$$\begin{array}{lcl}
\mbox{For } f(x)=x^2-1 \mbox{ and } g(x)=x-3 \mbox{ , calculate } g(f(2)).\\
\mbox{Note that } g(f(2)) \mbox{ means that we calculate } f(2) \mbox{ and we fill in this answer in function } g(x)\\
\mbox{Then}\\
f(2) = 2^2-1 = 4-1 = 3\\
\mbox{Hence } g(f(2)) = g(3)\\
g(3) = 3-3 = 0\\
\mbox{ So } g(f(2)) = 0


\end{array}$$

.
 Oct 30, 2014
 #1
avatar+2353 
+5
Best Answer

$$\begin{array}{lcl}
\mbox{For } f(x)=x^2-1 \mbox{ and } g(x)=x-3 \mbox{ , calculate } g(f(2)).\\
\mbox{Note that } g(f(2)) \mbox{ means that we calculate } f(2) \mbox{ and we fill in this answer in function } g(x)\\
\mbox{Then}\\
f(2) = 2^2-1 = 4-1 = 3\\
\mbox{Hence } g(f(2)) = g(3)\\
g(3) = 3-3 = 0\\
\mbox{ So } g(f(2)) = 0


\end{array}$$

reinout-g Oct 30, 2014

11 Online Users

avatar
avatar